A phase II study of afatinib treatment for elderly patients with previously untreated advanced non-small-cell lung cancer harboring EGFR mutations. (December 2018) - Imai, Hisao; Kaira, Kyoichi; Suzuki, Kensuke; Anzai, Masaki; Tsuda, Takeshi; Ishizuka, Tamotsu; Kuwako, Tomohito; Naruse, Ichiro; Nemoto, Kenji; Uchino, Junji; Morozumi, Nobutoshi; Ishihara, Shinichi; et al.
Highlights: This is the first study of first-line afatinib in EGFR mutated elderly patients. First-line afatinib of 30 mg/day is highly effective in this population. First-line afatinib of 30 mg/day has acceptable toxicity in this population. First-line afatinib could be a treatment option in this population. Abstract: Objective: The efficacy and safety of afatinib in elderly patients with EGFR -mutated non-small-cell lung cancer (NSCLC) have not been evaluated. This study aimed to assess the efficacy and safety of afatinib in elderly chemotherapy-naive patients with NSCLC harboring sensitive EGFR mutations. Materials and Methods: We prospectively assessed the clinical effects of afatinib as a first-line treatment for elderly (age ≥70 years) NSCLC patients with EGFR mutations (exon 19 deletion or exon 21 L858R mutation). All patients were initially administered afatinib (30 mg/day). Results: Between May 2014 and August 2017, 40 patients (13 men, 27 women) with adenocarcinoma were included in our analysis. The median age was 77 years (range, 70–85 years). The dose was reduced in 19 patients. The objective overall response and disease control rates were 72.5% and 100%, respectively, and the median progression-free survival and overall survival were 12.9 months and not reached, respectively. Common adverse events (AEs) included diarrhea, rash/acne, and anemia. Major grade 3 or higher toxicities included diarrhea (12.5%), mucositis (7.5%), and pneumonitis (7.5%). Afatinib treatment was discontinued in 8 patients owing to AEs of elevated amylase (n = 1), liver dysfunction (n = 1), rash/acne (n = 1), nail change (n = 1), anorexia (n = 2), pneumonitis (n = 2), and diarrhea (n = 2). Two patients died due to treatment-related pneumonitis. Conclusions: This is the first study that verified the efficacy and feasibility of first-line chemotherapy with afatinib at 30 mg/day in elderly patients with advanced NSCLC harboring sensitive EGFR mutations. First-line afatinib of 30 mg/day could be a treatment option in this patient population.